Chronic ethanol feeding promotes azoxymethane and dextran sulfate sodium-induced colonic tumorigenesis potentially by enhancing mucosal inflammation. Issue 1 (December 2016) - Shukla, Pradeep; Chaudhry, Kamaljit; Mir, Hina; Gangwar, Ruchika; Yadav, Nikki; Manda, Bhargavi; Meena, Avtar; Rao, RadhaKrishna
Abstract Background Alcohol consumption is one of the major risk factors for colorectal cancer. However, the mechanism involved in this effect of alcohol is unknown. Methods We evaluated the effect of chronic ethanol feeding on azoxymethane and dextran sulfate sodium (AOM/DSS)-induced carcinogenesis in mouse colon. Inflammation in colonic mucosa was assessed at a precancerous stage by evaluating mucosal infiltration of neutrophils and macrophages, and analysis of cytokine and chemokine gene expression. Results Chronic ethanol feeding significantly increased the number and size of polyps in colon of AOM/DSS treated mice. Confocal microscopic and immunoblot analyses showed a significant elevation of phospho-Smad, VEGF and HIF1α in the colonic mucosa. RT-PCR analysis at a precancerous stage indicated that ethanol significantly increases the expression of cytokines IL-1α, IL-6 and TNFα, and the chemokines CCL5/RANTES, CXCL9/MIG and CXCL10/IP-10 in the colonic mucosa of AOM/DSS treated mice. Confocal microscopy showed that ethanol feeding induces a dramatic elevation of myeloperoxidase, Gr1 and CD68-positive cells in the colonic mucosa of AOM/DSS-treated mice. Ethanol feeding enhanced AOM/DSS-induced suppression of tight junction protein expression and elevated cell proliferation marker, Ki-67 in the colonic epithelium. Conclusion This study demonstrates that chronic ethanol feeding promotes colonic tumorigenesis potentially by enhancing inflammation and elevation of proinflammatory cytokines and chemokines.